Youngest versus oldest child: why does mothers' snack choice differ?. (1st January 2020) - Damen, Femke W.M.; Steenbekkers, Bea L.P.A.; Fogliano, Vincenzo; Luning, Pieternel A.
Abstract: Young children frequently consume energy dense snacks, which is one of the factors contributing to childhood overweight. The consumption of more healthy snacks could help in meeting the dietary intake requirements of children. Previous research suggested that mothers of first children showed more health-conscious food behavior compared to mothers of not-first children. However, what is missing from earlier research is an in-depth exploration of differences in considerations to choose a snack and the reasons connected. Therefore, this study aims to characterize differences in mothers' snack choice for their youngest child at 2–3 years and their oldest child when he/she was of the same age. Moreover, this study aims to identify reasons for these differences. A grounded theory approach was used for data collection and analysis. Semi-structured interviews were carried out with 17 Dutch mothers with two or three children. All mothers indicated differences between snacks provided to their youngest child (2–3 years) and their oldest child when it was of the same age. Most frequently mentioned differences were youngest children receive unhealthy snacks at a younger age, the structure regarding snack providing is more fixed, and that youngest children receive less age-specific snacks. Most frequently mentioned reasons for these differences were role-modelling, novelty of the first-born, availability of other types of snacks at home, and school hours of the oldest child. The study provided insights into the possible role of siblings in shaping snack consumption. Results might be relevant for the development of intervention strategies to increase mothers' awareness and to help to meet children's dietary requirements.